Development of Etnosains Materials in 5E Cycle Learning Model Based on the Local Culture of Primary School Students - Sukenda Egok, Asep; Gurmani, Gurmani (Universitas Negeri Semarang, 2020)
This development research aims to develop valid and practical Ethnoscience Teaching Materials in the 5E Learning Cycle Model based on Local Wisdom of Elementary School Students. This type of research is Research and Development, adopting the Plomp development model which consists of three stages in developing, namely (1) preliminary research or preliminary analysis, (2) the prototyping phase or the design stage, and (3) the assessment phase. Data collection in research is interviews and questionnaires / questionnaires. The data analysis technique uses a Likert scale. The results showed that the media validation was classified as good with a percentage of 76.85%. The result of language validation is good with a percen tage of 71.43%. The results of the material validation category were very good with a percentage of 91.25%. Overall the results of the analysis and calculation of the questionnaire value from the expert team, Ethnoscience Teaching Materials in the 5E Learning Cycle Model based on Local Wisdom of Elementary School Students are in the very good category with a percentage of 80.33% meaning Ethnoscience Teaching Materials in the 5E Learning Cycle Model are based on Local Wisdom Elementary school students are valid and practical to use.